Co-Production Phases in the Development and Implementation of Digital Public Services - Mergel, Ines; Edelmann, Noella; Haug, Nathalie (Oxford University Press, 2025)
Public bureaucracies can be digitally transformed by using co-production approaches to design and develop digital public services with input from their stakeholders. Drawing on interviews with international digital transformation experts, this article explores what co-production looks like—conceptually and empirically. We are making a theoretical contribution to the existing co-production literature by identifying the roles different stakeholders play in each co-production phase and the work practices and approaches used to incorporate the stakeholders’ viewpoints. We show that service users’ input is not included continuously but selectively in the co-production phases of digital public services. Although digital public services are co-designed initially with the input of potential service users in the form of their user needs, the subsequent phases include different stakeholders up until the use phase, where service users are simultaneously using and evaluating the service. The results from this empirical study on the co-production of digital public services expand the existing co-production models—the co-production eco-system of stakeholders must be enlarged by the range of actors that need to be involved and the diverse roles they play in addressing citizen needs in a prospective, concurrent, and retrospective manner.
Keywords: co-production; public sector; digital public services; digital transformation; co-production phases; co-production roles; fi=Julkisjohtaminen|en=Public Management|